1983
DOI: 10.1177/014920638300900107
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Goal Change on Prominent Perceptions and Beha viors of Emplo yees

Abstract: A model exploring the hypothesized impact of goal change on employee perceptions and behaviors was examined. Aspects of goal change were found to be significantly related to satisfaction, organizational commitment, and absenteeism. Organizational commitment was found to be related to turnover, but neither satisfaction nor organizational commitment was found to have a significant relationship with absenteeism. The implications of these findings are discussed.There has been a great deal of research concerning bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Although research on the OCB–turnover relationship is limited, it has found that employees who exhibited lower levels of OCB were more likely to leave an organization than those who exhibited high levels of OCB (Chen, Hui, and Sego, 1998). With regard to the traditional withdrawal models, most of them point to individual‐level explanations for withdrawal behaviours (e.g., Hom and Griffith, 1991; Mobley, 1977), but some research has found that group factors can account for employees’ desire to withdraw from work through turnover (Abelson, 1983). According to Salancik and Pfeffer's (1978) social information processing theory (SIP), individuals receive cues from the surrounding social environment, form perceptions of the culture of the environment, and then act upon it.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Although research on the OCB–turnover relationship is limited, it has found that employees who exhibited lower levels of OCB were more likely to leave an organization than those who exhibited high levels of OCB (Chen, Hui, and Sego, 1998). With regard to the traditional withdrawal models, most of them point to individual‐level explanations for withdrawal behaviours (e.g., Hom and Griffith, 1991; Mobley, 1977), but some research has found that group factors can account for employees’ desire to withdraw from work through turnover (Abelson, 1983). According to Salancik and Pfeffer's (1978) social information processing theory (SIP), individuals receive cues from the surrounding social environment, form perceptions of the culture of the environment, and then act upon it.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Burton et al (2002) found no direct relation between (affective and continuance) commitment and overall absenteeism. In studies that consider the relation between organizational commitment and turnover (intention) as well as absenteeism (Angle & Perry 1981, Abelson 1983, Farrell & Petersen 1984, Shore et al 1990, Geurts et al 1999), a significant direct relation with absenteeism was either absent or much weaker than that between turnover and organizational commitment.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings also provide information for a better understanding of how subordinate business moral values relate to employee effectiveness when taking supervisor business moral values and perceived organizational moral values into consideration (Abelson, 1983;Hunt et al, 1989;Morris and Sherman, 1981). Follow-up research could investigate possible cross-level effects, such as those of organizational moral values, group moral norms, and individual moral values and behavior.…”
Section: Discussionmentioning
confidence: 81%